Danger Signaling in Atherosclerosis. Issue 2 (16th January 2015) - Zimmer, Sebastian; Grebe, Alena; Latz, Eicke
<x xml:space="preserve">Abstract</x> All aspects of the pathogenesis of atherosclerosis are critically influenced by the inflammatory response in vascular plaques. Research in the field of innate immunity from the past 2 decades has uncovered many novel mechanisms elucidating how immune cells sense microbes, tissue damage, and metabolic derangements. Here, we summarize which triggers of innate immunity appear during atherogenesis and by which pathways they can contribute to inflammation in atherosclerotic plaques. The increased understanding gained from studies assessing how immune activation is associated with the pathogenesis of atherosclerosis has provided many novel targets for potential therapeutic intervention. Excitingly, the concept that inflammation may be the core of cardiovascular disease is currently being clinically evaluated and will probably encourage further studies in this area.